MILLING QUALITY OF HULLED WHEAT BULGUR WITH STONE MILL - UNAL, H. GURAN; SACILIK, KAMIL (Wiley, 2011)
ABSTRACT In recent years, hulled wheat species have increased in importance because of their advantageous features as underutilized crops which have provided additional income to farmers and also contributed to agricultural diversification. Einkorn and emmer as two hulled wheat species have been used in this study. The milling quality of these hulled wheats was determined on fixed top stone and fixed bottom stone (FBS) mills at 1.75‐ and 2.5‐mm stone gap levels. The effects of parameters such as stone mill type, stone gap and milling quality of hulled wheat species have been studied. The obtained products have been classified as coarse (over 2 mm), medium (under 2 mm–over 1 mm), fine (under 1 mm) and husky. It reveals that FBS mill has ground in little particles and more unsteadily. This study also indicates that the grinding of emmer has brought along smaller particles due to its spindly structure and 1.75‐mm stone gap has been thought more acceptable because of the less husky product. PRACTICAL APPLICATIONHulled wheat species are very important due to their high nutrition potential. As compared with common wheat, hulled wheats are generally more resistant to diseases and have the ability to withstand drought so they can grow in harsh environments and poor soil. Hulled wheat is especially used for bulgur production because of its delicious taste. The milling operation is one of the most important steps in bulgur production. It needs abrasive mills because of its husky structure. In this study, milling quality of two hulled wheat (emmer and einkorn) bulgurs was determined on stone mills. We believe that the results of this research provide insights into the production of marketable bulgur and the choosing of suitable bulgur mill.
Keywords: 2. Zero hunger; 15. Life on land